2019
DOI: 10.1002/lno.11388
|View full text |Cite
|
Sign up to set email alerts
|

New guidelines for the application of Stokes' models to the sinking velocity of marine aggregates

Abstract: Numerical simulations of ocean biogeochemical cycles need to adequately represent particle sinking velocities (SV). For decades, Stokes' Law estimating particle SV from density and size has been widely used. But while Stokes' Law holds for small, smooth, and rigid spheres settling at low Reynolds number, it fails when applied to marine aggregates complex in shape, structure, and composition. Minerals and zooplankton can alter phytoplankton aggregates in ways that change their SV, potentially improving the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 94 publications
10
68
0
Order By: Relevance
“…9(1) page 7 of 24 regions were calculated using representative SVs of 100 and 500 m d -1 . Limited shipboard measurements of salp fecal pellets during EXPORTS showed SVs ranging hundreds of meters per day (D Steinberg, personal communication), similar to compilations of SV observations of sinking particles in the literature (e.g., Laurenceau-Cornec et al, 2019). Mean particle trajectories were computed from either the merged AVISO-ADCP velocity grid or the mean Revelle velocity time series.…”
Section: 1 Particle Source Funnel Modelingsupporting
confidence: 54%
“…9(1) page 7 of 24 regions were calculated using representative SVs of 100 and 500 m d -1 . Limited shipboard measurements of salp fecal pellets during EXPORTS showed SVs ranging hundreds of meters per day (D Steinberg, personal communication), similar to compilations of SV observations of sinking particles in the literature (e.g., Laurenceau-Cornec et al, 2019). Mean particle trajectories were computed from either the merged AVISO-ADCP velocity grid or the mean Revelle velocity time series.…”
Section: 1 Particle Source Funnel Modelingsupporting
confidence: 54%
“…The sinking speed of particles depends on their mineral composition (Le Moigne 2013), shape (Laurenceau et al, 2019) and on the phytoplankton community (Riley et al 2012, Guidi et al 2009. Consistent with our cytometric results, the pigment composition available at ST7, ST8 and ION show a community dominated by nanophytoplankton (>60% of total Chl-a) in the upper 80m, while diatoms were abundant at DCM depth (41-51% of total Chl-a, see Marañón et al 2020).…”
Section: Stemmann Et Al 2004)supporting
confidence: 84%
“…Type 2 is represented by the settling behaviour of thick disks presented in detail in the results section ( Fig. 3) and has been observed in this study for Re ul ∈ (20,44) and Fr ul ∈ (1, 1.6). It is characterized by a tilted position in phase III, detachment of a wake and a bell-shaped structure on a jet, which is specific for this type and has not been observed for the other two types described herein.…”
Section: Discussionsupporting
confidence: 53%
“…It has been already demonstrated that standard formulas for particles settling in a homogeneous water column misestimate considerably the settling velocity and the residence time of spheres 24 and disks 39 , since they do not take into account the fact that density gradient in the column of fluid enhances drag acting on a particle. Moreover, researchers are more and more aware that oversimplifications of marine particles shape and density as well as the application of Stokes’ Law, which is dedicated to the settling of a sphere in the laminar Re number regime, may be the source of unreliable estimation of particulate flux in ocean models 44 , 45 . Better understanding of the dynamics of variously shaped particles settling in stratified systems is necessary to facilitate development of robust modelling approaches.…”
Section: Introductionmentioning
confidence: 99%